RETRACTED: Comparative Analysis of Trade Liberalization, CO2 Emissions, Energy Consumption and Economic Growth in Southeast Asian and Latin American Regions: A Structural Equation Modeling Approach - Zeeshan, Muhammad; Han, Jiabin; Rehman, Alam; Ullah, Irfan; Afridi, Fakhr E. Alam; Fareed, Zeeshan (Frontiers in Environmental Science, 2022)
This study compares the nexus among trade liberalization, CO2 emissions, energy consumption, and economic growth in Southeast Asian and Latin American Countries. We apply the Structural Equation Modeling approach for estimation analysis of the data from 1991-2018. The empirical findings of this study validate that trade has a positive and statistically significant effect on energy consumption, CO2 emissions, and GDP in Southeast Asian countries. While in Latin American countries, trade shows a positive insignificant impact on energy consumption, but the coefficients for both CO2 emissions and GDP are positive and statistically significant. Energy consumption also exhibits a positive significant effect on CO2 emissions and a positive statistically insignificant effect on GDP in the Southeast Asian region. However, in Latin American countries, energy consumption predicts a positive and statistically significant impact on both CO2 emissions and GDP. While CO2 emissions indicate a positive significant effect on GDP in both regions. Therefore, each country’s government in both areas should formulate appropriate policies to promote green technologies in the production and exports, which could help economies to achieve a clean environment and sustainable long-term development.